2020
DOI: 10.3389/fpsyg.2020.00474
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Beliefs About Children’s Anger and Skill in Recognizing Children’s Anger Expressions

Abstract: Everyday beliefs often organize and guide motivations, goals, and behaviors, and, as such, may also differentially motivate individuals to value and attend to emotion-related cues of others. In this way, the beliefs that individuals hold may affect the socioemotional skills that they develop. To test the role of emotion-related beliefs specific to anger, we examined an educational context in which beliefs could vary and have implications for individuals' skill. Specifically, we studied 43 teachers' beliefs abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…First, studies using the pilot version of this measure with adult faces have demonstrated expected associations with other measures of emotion recognition and knowledge (Castro, Halberstadt, & Garrett-Peters, 2016), the typical gender difference of girls performing more accurately than boys (Rehder et al, 2017), higher scores for second-grade children thought to be typically developing compared to children with conduct problems and callous/unemotional behaviors (Rehder et al, 2017), and longitudinal effects of hyperactivity on emotion recognition (Castro, Cooke, et al, 2018). Second, teachers who report valuing children’s anger in educational settings also demonstrated anger accuracy on the PerCEIVED task (Hagan et al, 2020). Third, with regard to emotion bias, studies have focused on anger and the degree to which misperception of anger is differentially imposed on Black compared to White faces; this phenomenon has now been verified in the similar measure with adult faces (Halberstadt et al, 2018), as well as the PerCEIVED task with child faces and in several studies with various populations (Cooke, 2020; Halberstadt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, studies using the pilot version of this measure with adult faces have demonstrated expected associations with other measures of emotion recognition and knowledge (Castro, Halberstadt, & Garrett-Peters, 2016), the typical gender difference of girls performing more accurately than boys (Rehder et al, 2017), higher scores for second-grade children thought to be typically developing compared to children with conduct problems and callous/unemotional behaviors (Rehder et al, 2017), and longitudinal effects of hyperactivity on emotion recognition (Castro, Cooke, et al, 2018). Second, teachers who report valuing children’s anger in educational settings also demonstrated anger accuracy on the PerCEIVED task (Hagan et al, 2020). Third, with regard to emotion bias, studies have focused on anger and the degree to which misperception of anger is differentially imposed on Black compared to White faces; this phenomenon has now been verified in the similar measure with adult faces (Halberstadt et al, 2018), as well as the PerCEIVED task with child faces and in several studies with various populations (Cooke, 2020; Halberstadt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This sample included 43 fourth- and fifth-grade teachers participating in a larger study (see also Hagan et al, 2020). Teachers received $40 compensation for their time (IRB #11681).…”
Section: Methodsmentioning
confidence: 99%
“…One growing and exciting area of emotion perspectives research involves the emotion perspectives that individuals have of others' emotions. Except for research on parents' and teachers' beliefs about children's emotions (e.g., Hagan et al, 2020;Halberstadt et al, 2013), this is a relatively understudied area of emotion perspectives research, notably with regard to beliefs concerning emotion malleability/controllability which is otherwise a robust area of study. In the current special issue, Smith and colleagues present research that addresses these gaps in the literature to examine if there is a potential cost to holding stronger beliefs in the controllability of emotion, and specifically controllability beliefs about others' emotions (Smith et al, 2023).…”
Section: Overview Of Papers and Research Themes Included In The Speci...mentioning
confidence: 99%
“…These recursive processes of action-internalization and the representation of emotion are articulated in daily socialization activities and early childhood education, both in institutionalized education [4,5] (notably preschools) and in family education [6]. These spaces of formal and informal education transmit norms-explicitly or implicitly-that indicate emotional guidelines expressed in language about what is expected or desirable in a social context, which are then culturally reinforced [7].…”
Section: Culture and Mechanisms Of Emotional Socializationmentioning
confidence: 99%